PROJECT FUTURE IN SOCIO AFFECTIVE DIMENSION: HOW TO BUILD THE PERCEPTIONS OF STUDENTS SECONDARY EDUCATION IN PORTUGAL AND HIGH SCHOOL IN BRAZIL - Marilia Frassetto de Araujo; Célia Regina Rossi; Maria Filomena Rodrigues Teixeira; Paula Regina Costa Ribeiro (Editora da Universidade de Santa Cruz do Sul, 2016)
This research aimed to understand how the "future project" regarding the socio-affective dimension is built by high school students in Portugal and in Brazil. The project was based on the concept of culture and adolescence as a cultural construction. The definition of future project was adopted in the above mentioned dimension characterized by defining affections and passions. Through focus groups with adolescents it was possible to analyze their narratives about the future project on the socio-affective dimension; to get to know the speeches produced by them on issues regarding sexuality, gender and and sexual diversity. The survey found out that most adolescents had projects for their future. Moreover, it pointed out the differences that permeate several boys' and girls' behaviors. It was concluded that the questioning of these issues from ethical questions that allow teenagers to reflect on their relationships among peers, in the community, with family, responsibility and criticality is essential. And education is central to this process.